Rua Dr. Assis: uma incursão pela paisagem patrimonial transfigurada da Cidade Velha, Belém do Pará - TUTYIA, Dinah Reiko (Universidade Federal do Pará, 2017)
This research investigate Dr. Assis street landscape transformation – located in Cidade Velha neighborhood of Belém – based on rereading of buildings its classified as "renewal" by the Law 7.709 of 1994. This law is responsible for Belém’s protection and preservation Historic, Artistic, Environmental and Cultural Heritage. The “renewal” category fits the properties with no interest of preservation, which can be replaced by new ones. Thus these lots in the historic center, “opens custody” to the dynamics of transformation, a city's intrinsic characteristic. The transfigured landscape which escapes from the “cultural heritage aesthetic” consolidates a new “Cidade Velha” – Belém’s genesis district – which along with Campina are the city’s Historic Center. Based on street ethnography method, an incursion is made into this landscape, which keeps in its, the building’s materiality and in the memories of the local residents and traders, the transformer process of the protected urban fabric. Thus, the space (re) cognition, aims to bring out the material-immaterial relation, eclipsed by the legislation category of 1994.